Assessing Adherence and Barriers to Long-Term Elimination Diet Therapy in Adults with Eosinophilic Esophagitis - Wang, Ryan (Dig Dis Sci, 2018)
BACKGROUND: The six-food elimination diet (SFED) is an effective treatment approach for eosinophilic esophagitis (EoE), but it can be challenging and affect patients’ quality of life. AIM: Assess patients’ long-term adherence to SFED and potential factors influencing adherence. METHODS: EoE patients were recruited online via multiple platforms. Patients were classified as reaching the maintenance stage if they responded to SFED and identified specific trigger foods by reintroduction. Maintenance stage patients were categorized into those actively following the elimination diet (ACTIVE) and those no longer on their prescribed diet (FORMER). Participants completed a study-specific questionnaire assessing patient experiences related to SFED use. RESULTS: Forty-two participants were identified as having reached the SFED’s maintenance stage. 57% (24/42) of the maintenance stage patients were ACTIVE users. FORMER users rated the SFED’s effectiveness at treating symptoms (5.45 ± 3.96, 10 max.) lower than ACTIVE users (8.29 ± 2.76, p = .02). A greater percentage of FORMER users (100%) agreed social situations create challenges in following the diet compared to ACTIVE users (67%, p < .05). Anxiety related to SFED was also higher among FORMER users (64%) compared to ACTIVE users (21%, p < .01). Both ACTIVE (95.8%) and FORMER (81.8%, NSS) users would recommend the elimination diet to other EoE patients. CONCLUSIONS: Understanding SFED adherence is multifactorial and complex. Factors influencing SFED adherence during long-term maintenance with diet therapy include diet effectiveness, social situations, and diet-related anxiety. Despite a lower than expected long-term adherence to maintenance of an elimination diet, the majority would recommend diet therapy as a treatment to other EoE patients.